A Simple Method for the Fabrication of Metallic Copper Nanospheres-Decorated Cellulose Nanofiber Composite. Issue 7 (July 2016) - Bang, Hyunsik; Ma, Ke; Wei, Kai; Kang, Chang-Yong; Kim, Byoung-Suhk; Gopiraman, Mayakrishnan; Lee, Jung Soon; Kim, Ick-Soo
Graphical Abstract: Abstract : Herein, we report a new and simple method for the preparation of metallic copper nanospheres-decorated cellulose nanofiber composite (CuNSs/CNFs). Initially, the cellulose acetate nanofibers (CANFs) were electrospun followed by deacetylation and anionization to produce functional anionic cellulose nanofibers ( f -CNFs). The CuCl2 precursor was deposited on the f -CNFs (CuCl2 /CNFs) by a simple dipping method. Then the CuCl2 /CNFs were reduced under vacuum by using aluminum foil to produce the CuNSs/CNFs. The resultant CuNSs/CNFs composite was characterized by various microscopic and spectroscopic methods. Fourier transform infrared spectroscopy (FT-IR) confirmed the successful functionalization of anionic groups with the CNFs. The field emission scanning electron microscopy (FE-SEM) and transmission electron microscope (TEM) results confirmed the formation of CuNSs on the surface of CNFs. From the scanning electron microscopy-energy dispersive spectroscopy (SEM-EDS) analysis, the weight percentage of Cu was found to be 23.5 wt%. The successful reduction of CuO to metallic Cu was confirmed by X-ray photoemission spectroscopy (XPS) and X-ray diffraction (XRD) analyses. Mechanism has been proposed for the formation of metallic Cu sphere on CNFs.